On sand samples from the west coast of Greenland I. An examination of the contents of minerals in a number of sand samples from the northern part of the Holsteinsborg district - Thomsen, Bruno (Meddelelser om Grønland, 1957)
Forty one samples of sand from rivers and beaches from three fjords north of Holsteinsborg were analysed. On the basis of the minerals of the heavy fractions the samples may be divided into three groups: group E derived from enderbitic gneiss with the main minerals, hornblende, hypersthene, and diopside, while garnet plays a secondary role only; group G chiefly derived from granulitic rocks where garnet is dominating with sillimanite and rutile as characteristic components, while the content of hornblende, hypersthene, and diopside is relatively low and, finally, group ]VI that with the main minerals, hornblende, hypersthene, diopside, and garnet and a slight content of sillimanite and rutile shows that the sample material derives from enderbitic as well as granulitic rocks.